Polyunsaturated fatty acids in various macroalgal species from north Atlantic and tropical seas - van Keulen Herman; de Visser Willem; Helsper Johannes PFG; van Ginneken Vincent JT; Brandenburg Willem A (Lipids in Health and Disease, 2011)
Abstract Background In this study the efficacy of using marine macroalgae as a source for polyunsaturated fatty acids, which are associated with the prevention of inflammation, cardiovascular diseases and mental disorders, was investigated. Methods The fatty acid (FA) composition in lipids from seven sea weed species from the North Sea ( Ulva lactuca, Chondrus crispus, Laminaria hyperborea, Fucus serratus, Undaria pinnatifida, Palmaria palmata, Ascophyllum nodosum ) and two from tropical seas ( Caulerpa taxifolia, Sargassum natans ) was determined using GCMS. Four independent replicates were taken from each seaweed species. Results Omega-3 (n-3) and omega-6 (n-6) polyunsaturated fatty acids (PUFAs), were in the concentration range of 2-14 mg/g dry matter (DM), while total lipid content ranged from 7-45 mg/g DM. The n-9 FAs of the selected seaweeds accounted for 3%-56% of total FAs, n -6 FAs for 3%-32% and n -3 FAs for 8%-63%. Red and brown seaweeds contain arachidonic (C20:4, n-6) and/or eicosapentaenoic acids (EPA, C20:5, n-3), the latter being an important "fish" FA, as major PUFAs while in green seaweeds these values are low and mainly C16 FAs were found. A unique observation is the presence of another typical "fish" fatty acid, docosahexaenoic acid (DHA, C22:6, n-3) at ≈ 1 mg/g DM in S. natans . The n-6: n-3 ratio is in the range of 0.05-2.75 and in most cases below 1.0. Environmental effects on lipid-bound FA composition in seaweed species are discussed. Conclusion Marine macroalgae form a good, durable and virtually inexhaustible source for polyunsaturated fatty acids with an (n-6) FA: (n-3) FA ratio of about 1.0. This ratio is recommended by the World Health Organization to be less than 10 in order to prevent inflammatory, cardiovascular and nervous system disorders. Some marine macroalgal species, like P. palmata , contain high proportions of the "fish fatty acid" eicosapentaenoic acid (EPA, C20:5, n-3), while in S. natans also docosahexaenoic acid (DHA, C22:6, n-3) was detected.